Volatilitas Harga Saham: Leverage, Ukuran Perusahaan, Pertumbuhan Aset - Hasna Rosyida; Amrie Firmansyah; Setyo Baskoro Wicaksono (LPPM ISNJ Bengkalis, 2020)
This study examines the effect of leverage, company size, and asset growth on stock price volatility. This study uses data from all companies listed on the LQ45 index (BEI) from 2017 to 2019. Based on purposive sampling, this study obtained 31 financial statement data so that the final sample in this study amounted to 93 firm-year observations. Data analysis was analyzed using multiple regression analysis with Eviews 10 software. The study results concluded that leverage has a positive effect on stock price volatility, company size has a negative effect on stock price volatility, and asset growth has no effect on stock price volatility. This study's results can be used as material for management evaluation in increasing share prices so that this condition can attract investors' interest in investing in the company.